Lumpfish, Cyclopterus lumpus, distribution in the Gulf of Maine, USA: observations from fisheries independent and dependent catch data - Fairchild, Elizabeth A.; Wulfing, Sophie; White, Easton R. (PeerJ, 2024)
The Gulf of Maine (GoM) is one of the fastest-warming parts of the world’s oceans. Some species’ distributional shifts have already been documented, especially for commercially-important species. Less is known about species that are not currently exploited but may become so in the future. As a case study into these issues, we focus on lumpfish (Cyclopterus lumpus) because of the recognized and timely need to understand wild lumpfish population dynamics to support sustainable fisheries and aquaculture developments. Using occurrence data from five different fisheries-dependent and independent surveys, we examined lumpfish distribution over time in the GoM. We found that lumpfish presence was more likely in Fall and correlated with deeper waters and colder bottom temperatures. Since 1980, lumpfish presence has increased over time and shifted north. Given a limited set of data, these findings should be interpreted with caution as additional work is needed to assess if the actual distribution of lumpfish is changing. Nevertheless, our work provides preliminary information for resource managers to ensure that lumpfish are harvested sustainably for use in emergent lumpfish aquaculture facilities.
Keywords: Range shift; Aquaculture; Water temperature; Lumpfish; Data limited species; Species range shift; Gulf of Maine; Fisheries